Pengaruh Pengangguran Terhadap Pertumbuhan Ekonomi - Irawan Irawan; Puput Iswandyah Raysharie; Tesalonika Tesalonika; Diah Septianingsih; Muhammad Samman; Muhammad Satrio; Novita Sari; Siti Pahrun Nisa; Zulkarnain Zulkarnain (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Palangkaraya's economic growth to date has only reached 2.95%. The aim of this study is to examine the magnitude of the increase in unemployment rates and its impact on economic progress. Variable X1: effect of unemployment, X2: unemployment and Y: economic growth. Literature studies were used in this research using a number of journals as a focus point for analysis and comparing research results. A number of studies show how high unemployment rates affect economic growth.